AKTIVITAS AMILASE, PROTEASE dan LIPASE DARI MADU LEBAH Trigona sp, Apis mellifera dan Apis dorsata - Hendric Surya Putra; Winni Astuti; Rudi Kartika (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2018)
Activities of amylase, protease and lipase from honey Trigona sp, Apis mellifera and Apis dorsata, determination protein concentration and the activity protease done with Bradford method, the determination of the glucose standard and activity amylase done with 3,5-dinitro salicylic acid (DNS) method and activity lipase done with acid-base titration with coconut oil substrate. The honey from Trigona sp has value of the activity amylase and lipase respectively by 0,0136 U / mg and 0,359 U/mg, whereas honey Apis mellifera has activity of protease, amylase and lipase of each 1,22 x 10-6 U/mg; 0,944 U/mg and 0,304 U/mg and then honey Apis dorsata has amylase and lipase activity of each of 0,0645 U/mg and 0,287 U/mg.